One succeeds and the other fails? Criminal justice in times of emergency - Vaczi, Peter (Frontiers in Political Science, 2025)
The Government has declared a state of emergency for the whole territory of Hungary for a period of 210 days from 1 November 2022 in view of the armed conflict and humanitarian disaster in Ukraine and to avert and manage the consequences of such conflicts in Hungary. Under the rules of emergency legislation, the Government is thus once again in a constitutional position to suspend the application of certain laws, derogate from statutory provisions and take other extraordinary measures. On the basis of this authorization, Government Decree 3/2023 (I. 12.) on the different application of certain provisions concerning the execution of sentences during a state of emergency was adopted at the beginning of the year, according to which, upon the request of a non-Hungarian convict, the national commander of the penitentiary system shall suspend the execution of the sentence until the transfer of the sentence, provided that certain conditions are met and there are no grounds for exclusion. Based on a detailed analysis of the legislation, it can be concluded that in practice this may also mean the remission of the remaining part of the sentence, since the receiving foreign state must ensure the enforcement of the sentence under Hungarian rules, but it is questionable whether this will be done. This outcome, however, runs counter to the fundamental principle of criminal justice, the principle of proportionate punishment, as it discriminates between offenders based on nationality. How compatible is this solution with the fundamental principles of the rule of law, such as non-discrimination or the principle of the obligation to be punished?